ASSESSMENT PRACTICE IN A LANGUAGE CENTER IN THE UANL - Licona Luna, Milton Raúl; Alvarado Martínez, Elizabeth (Universidad Autónoma de Nuevo León, 2020)
Institutions from basic to higher education in Mexico that offer courses of English as a Foreign Language rely heavily on the administering of assessment, usually the type that is formal. However, the literature shows how important it is the involvement of other types of assessment in the classroom for effective language learning to take place. For instance, assessment for learning, which consist of a continuous assessment where learners receive feedback so greater learning occurs, what is more, it enables teachers to modify their teaching ways as they reflect on the learners’ progress. To show how assessment is carried out in our context, this research project focuses on a case study within the CAADI from FOD in the UANL.